Implementation of a clinical pharmacy service to an allogeneic stem cell transplant ambulatory clinic. (September 2014) - Chieng, Ruth; Coutsouvelis, John; Poole, Susan; Dooley, Michael J.; Booth, Diana
Abstract: Allogeneic stem cell transplantation (SCT) is a complex procedure that requires specialized medication management. Providing clinical pharmacy services in the ambulatory setting is warranted, as medications are a common source of confusion for SCT patients and their carers. These patients were routinely managed via traditional ambulatory dispensary services. The successful implementation of a clinical pharmacy service to the SCT unit ambulatory clinic allowed for regular contact and review by an experienced clinical pharmacist. This new service was evaluated within the context of a research project. The clinical pharmacist's presence in the ambulatory setting resulted in the identification and rectification of many medium to high risk medication related problems. The clinical pharmacist also contributed towards improved overall adherence. Other institutions are encouraged to implement and evaluate clinical pharmacy services to their ambulatory settings for SCT and other complex chronic patients.